2003
DOI: 10.1113/eph8802543
|View full text |Cite
|
Sign up to set email alerts
|

Nitric Oxide‐Dependent in vitro Secretion of Amylase from Innervated or Chronically Denervated Parotid Glands of the Rat in Response to Isoprenaline and Vasoactive Intestinal Peptide

Abstract: The basal in vitro release of amylase was similar from rat parotid lobules of innervated and chronically denervated glands and was unaffected by the inhibitors used in this study. The secretion of amylase induced by isoprenaline or vasoactive intestinal peptide (VIP) was reduced by one‐third to one‐half from the lobules of the innervated glands and even more so from the lobules of the denervated glands by ODQ, an inhibitor of soluble guanyl cyclase which is activated by nitric oxide (NO) and catalyses the cGMP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
16
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 29 publications
1
16
0
Order By: Relevance
“…It is well known that the main signaling pathway underlying amylase secretion through VIP receptors in normal parotid cells proceeds via cAMP [15,16]. Concentrations of VIP higher than those used here were shown to stimulate amylase secretion in rat parotid glands in vitro [17], and most reports on VIP stimulation of cAMP at concentrations similar to those used here refer to dispersed cultured parotid acinar cells rather than whole glands [15,16]. Comparing in vivo concentrations of VIP in the extracellular fluid of gastrointestinal tract after parasympathetic stimulation (about 10 À10 M) [18] with the concentration range for ex vivo VIP-induced NO-mediated regulation of amylase shown here, it is conceivable that such an inhibitory mechanism on amylase secretion might protect the exocrine cells from secreting high amounts of protein at concentrations of VIP higher than physiological.…”
Section: Discussionmentioning
confidence: 80%
“…It is well known that the main signaling pathway underlying amylase secretion through VIP receptors in normal parotid cells proceeds via cAMP [15,16]. Concentrations of VIP higher than those used here were shown to stimulate amylase secretion in rat parotid glands in vitro [17], and most reports on VIP stimulation of cAMP at concentrations similar to those used here refer to dispersed cultured parotid acinar cells rather than whole glands [15,16]. Comparing in vivo concentrations of VIP in the extracellular fluid of gastrointestinal tract after parasympathetic stimulation (about 10 À10 M) [18] with the concentration range for ex vivo VIP-induced NO-mediated regulation of amylase shown here, it is conceivable that such an inhibitory mechanism on amylase secretion might protect the exocrine cells from secreting high amounts of protein at concentrations of VIP higher than physiological.…”
Section: Discussionmentioning
confidence: 80%
“…The inhibition of the neuronal type NO‐synthase by the use of N‐PLA did not reduce the volumes of parotid saliva produced by the activation of either α‐or β‐adrenoceptors in response to the stimulation of the sympathetic innervation. The lack of an effect by N‐PLA on the nerve‐evoked β‐mediated volume response combined with the previously reported reduction in the isoprenaline‐evoked β‐mediated in vitro secretion of amylase upon administration of N‐PLA (Sayardoust & Ekström, 2003), suggests that the two phenomena are non‐uniformly influenced by the inhibition of NO generation. The lowered fluid response to the stimulation of the sympathetic innervation upon administration of l ‐NAME in the presence of α‐adrenoceptor blockade was most likely due to impaired blood flow through the gland (Anderson & Garrett, 1998).…”
Section: Discussionmentioning
confidence: 87%
“…Intracellularly, NO activates soluble guanyl cyclase to catalyse the formation of cyclic GMP, and by preventing NO from activating this enzyme, the isoprenaline evoked in vitro secretion of amylase from rat parotid gland tissue is markedly reduced (Sayardoust & Ekström, 2003). Since in the rat parotid gland, cyclic GMP may reduce the rate of enzymatic degradation of cyclic AMP by inhibiting the activity of phosphodiesterases (Imai et al 1995), there is the possiblity that the NO/cyclic GMP pathway contributes to elevated levels of cyclic AMP in the glands.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors suggested involvement of the NOS-cyclic GMP pathway in the SNI-2011-induced amylase secretion from parotid acinar cells. Activation of ␤-adrenoceptors and VIP receptors likely causes amylase secretion from the rat parotid glands partly through a NO/cyclic GMP-dependent intracellular pathway involving the activity of nNOS, possibly of acinar origin (Sayardoust and Ekstrom, 2003).…”
Section: Secretion and Neurogenic Nitric Oxidementioning
confidence: 99%